Bodies As Evidence : Security, Knowledge, and Power. - Maguire, Mark.; Rao, Ursula; Zurawski, Nils. (Durham : Duke University Press, 2018)
Through global case studies that explore biometric identification, border control, forensics, militarized policing, and counterterrorism, the contributors show how bodies have become critical sources of evidence that is organized and deployed to classify, recognize, and manage human life.
Cover -- Contents -- Introduction: Bodies as Evidence -- 1. The Truth of the Error: Making Identity and Security through Biometric Discrimination -- 2. Injured by the Border: Security Buildup, Migrant Bodies, and Emergency Response in Southern Arizona -- 3. E-Terrify: Securitized Immigration and Biometric Surveillance in the Workplace -- 4. "Dead-Bodies-at-the-Border": Distributed Evidence and Emerging Forensic Infrastructure for Identification -- 5. The Transitional Lives of Crimes against Humanity: Forensic Evidence under Changing Political Circumstances -- 6. Policing Future Crimes -- 7. "Intelligence" and "Evidence": Sovereign Authority and the Differences That Words Make -- 8. The Secrecy/Threat Matrix -- 9. What Do You Want? Evidence and Fantasy in the War on Terror -- Conclusion: Discontinuities and Diversity -- Contributors -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- Z.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books